Toxoplasma gondii seroprevalence in the Portuguese population: comparison of three cross-sectional studies spanning three decades. Issue 10 (5th October 2016) - Gargaté, Maria João; Ferreira, Idalina; Vilares, Anabela; Martins, Susana; Cardoso, Carlos; Silva, Susana; Nunes, Baltazar; Gomes, João Paulo
Abstract : Background: Toxoplasma gondii is an obligate intracellular protozoan infecting up to one-third of the world's population, constituting a life threat if transmitted from mother to child during pregnancy. In Portugal, there is a lack of knowledge of the current epidemiological situation, as the unique toxoplasmosis National Serological Survey was performed in 1979/1980. Methods: We studied the seroprevalence trends in the Portuguese general population over the past 3 decades, by assessing chronological spread cross-sectional studies, with special focus on women of childbearing age, by age group, region and gender. Results: The T. gondii overall seroprevalence decreased from 47% in 1979/1980 to 22% (95% CI 20% to 24%) in 2013. Generally, we observed that the prevalence of T. gondii IgG increased significantly with age and it decreased over time, both in the general population and in the childbearing women (18% prevalence in 2013). Conclusions: The scenario observed for the latter indicates that more than 80% of childbearing women are susceptible to primary infection yielding a risk of congenital toxoplasmosis and respective sequelae. Since there is no vaccine to prevent human toxoplasmosis, the improvement of primary prevention constitutes a major tool to avoid infection in such susceptible groups.